Alkali Metal Chloride‐Doped Water‐Based TiO2 for Efficient and Stable Planar Perovskite Photovoltaics Exceeding 23% Efficiency. Issue 12 (27th October 2021) - Gao, Feng; Luo, Chao; Wang, Xianjin; Zhao, Qing
Abstract: TiO2 is one of the most broadly employed electron transport materials in n‐i‐p structure perovskite solar cells (PSCs). Low‐temperature non‐hydrolyzed sol–gel method is developed to prepare TiO2 in order to simplify the fabrication process and match with the planar structure PSCs. Conventional low‐temperature TiO2 film using organic solvents as dispersants makes direct doping challenging due to limited solubility. Here, a newly developed water‐based TiO2 solution is directly doped with different alkali chlorides, resulting in better conductivity, compatible energy level matching, and enhanced charge extraction in terms of electron transport layer (ETL) for PSCs. As a result, a power conversion efficiency of 23.15% is achieved based on NaCl‐doped TiO2 with competitive storage stability and light stability. The water‐based TiO2 ETL for more general doping of various solutes opens up a new avenue for environmental‐friendly manufacturing superior ETL toward high‐efficiency and stable perovskite photovoltaic devices. Abstract : Photovoltaic performance of perovskite solar cells (PSCs) based on low‐temperature TiO2 has not yet reached the mainstream level. Direct doping of alkali metal chloride into water‐based TiO2 is found to effectively improve the charge transport and extraction capabilities. The planar PSCs with NaCl‐doped TiO2 demonstrate a record efficiency of 23.15%, exhibiting a 4100 h storage stability.